Pengaruh Strategi Pemasaran, Kualitas Pelayanan, Dan Kepuasan Pelanggan Terhadap Produk Kredit Usaha (KUR) Pada Pegadaian Cp Dinoyotangsi Surabaya - Fitri Setiyaningsih; Dwi Agung Cahya; Andi Bhakti Akbar; Chamariyah Chamariyah (Universitas 45 Surabaya, 2025)
Abstract This type of research is explanatory research, the research approach uses a quantitative approach, data analysis using SPSS. The research sample was 50 employees. The objectives of this study are 1). To test and analyze the simultaneous influence between marketing strategy, service quality, and customer satisfaction on product interest People's business credit (KUR) Pegadaian CP Dinoyotangsi Surabaya Branch. 2). To test and analyze the relationship between the influence of marketing strategies and KUR products at Pegadaian CP Dinoyotangsi Surabaya Branch. 3). To test and analyze the relationship between the effect of service quality and KUR products at the Pawnshop CP Dinoyotangsi Surabaya Branch. 4). To test and analyze the relationship between the effect of customer satisfaction on KUR products at the Pawnshop CP Dinoyotangsi Surabaya Branch. 5). To test and analyze which variables among marketing strategies, service quality, and customer satisfaction have an interest in People's Business Credit (KUR) products at Pegadaian CP Dinoyotangsi Branch Surabaya. The results showed that: 1). Simultaneously, marketing strategy, service quality, and customer satisfaction have an impact on product interest in People's Business Credit (KUR) at Pegadaian CP Dinoyotangsi Surabaya Branch. evident from the results of the calculated F value of 20,740 with a significance level known from the sig value of 0.004 (smaller than 0.05). 2). Partially, marketing strategy, service quality, and customer satisfaction have an interest in people's business credit (KUR) products at the Surabaya Dinoyotangsi Branch Pawnshop. 3). Based on the results of the t test, it is known that customer satisfaction has a dominant effect on KUR products at the CP Pawnshop Dinoyotangsi Surabaya Branch, as evidenced by the t value of 2.045 with a significance level of 0.004 (smaller than 0.05).